CARING FOR RELIGIOUS MODERATION THROUGH THE MANAGEMENT OF SOCIAL MEDIA ON THE SALATIGA CAMPUS AS THE CITY OF TOLERANCE - Wuri Arenggoasih; Nova Mega Pertiwi (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Awareness of religious moderation is an important value in Salatiga City as the most tolerant city in 2021. The city has two religious universities, namely IAIN Salatiga and Satya Wacana Christian University. Through social media accounts on Instagram, both universities disseminate information about the existence of the institution. Assuredly, social media management is the main thing in content management, especially regarding religious moderation as a form of religious tolerance in Salatiga. Therefore, this study aims to determine how the social media management of both universities related to religious moderation includes planning, organizing, actuating, and controlling through the case study method.As an educational institution in one field, the awareness to maintain and realize the City of Harmony - Salatiga City with an attitude of religious moderation has been implemented through postings on their Instagram platform. Social media management is not only manifesting religious moderation as a planned image but a practice of daily life. The posts of universities are the result of joint thinking in their respective public relations departments through a brand story strategy with validation before being uploaded.